Une nouvelle espèce d'Ampelisca (Crustacea,Amphipoda) des côtes du Portugal (Atlantique Nord-Est): Ampelisca lusitanica n.sp - Bellan-Santini, D.; Marques, J.C. (Cahiers de Biologie Marine, 1987)
Ampelisca lusitanica is characterized by : the antenna formula (peduncle A2 < A1 < A2; A2 < 1/2 body); the size of the head shorter than 3 first segments of the pereion combined; the shape of ep3 with the postero-distal comer rounded-quadrate; merus of Pereiopod 7 with an anterior peg-like process projected beyond the carpus; U1 and U2 with spinose rami and U3 with the inner margin of the inner ramus denticulate (10 to 12 denticulations). Ampelisca lusitanica is compared with Ampelisca species having an U3 denticulate or serrulate and especially with Ampelisca unidentata.
Ant'Phipoda Literature database